Outcomes of anterior cruciate ligament reconstruction surgery from private and public healthcare services in AustraliaKey points - Thomas J. West; Andrea M. Bruder; Kay M. Crossley; Michael A. Girdwood; Laura K. To; Jamon L. Couch; Mark J. Scholes; Sebastian C.S. Evans; Melissa J. Haberfield; Christian J. Barton; Ewa M. Roos; Alysha De Livera; et al. (JSAMS Plus)
Objective: To explore outcomes of anterior cruciate ligament (ACL) reconstructive surgery (ACLR) between individuals using private and public healthcare. Methods: We conducted a cross-sectional study of participants, 9–36 months post-ACLR using public or private healthcare services. Multivariable linear regression assessed the association between healthcare service used (private versus public) with self-reported outcomes (Knee injury and Osteoarthritis Outcome Score (KOOS) subscales of pain, symptoms, sport/recreation, knee-related quality of life (QoL); 0–100 scale), adjusting for potential confounders. Results: A total of 314 participants were included (median age 29 years, 35 ​% female). One hundred and thirty-nine (44 ​%) underwent ACLR using private healthcare. Individuals using private healthcare for ACLR reported better post-ACLR knee-related QoL (mean difference 5.1; 95%CI 0.6 to 9.7) than individuals using public healthcare, when adjusted for available confounders. No other KOOS subscale scores (pain, symptoms, sport/recreation) differed between healthcare groups in our adjusted analysis. Conclusions: Australian young adults who underwent ACLR using private healthcare (compared to public healthcare) services reported better knee-related QoL post-operatively in this cross-sectional cohort. Sociodemographic and socioeconomic factors contributed little to the differences observed. Future research should consider potential disparities in outcomes between participants using differing healthcare services both clinically and when recruiting participants into research studies evaluating outcomes post-ACLR.